Rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone with or without radiotherapy in primary mediastinal large b-cell lymphoma: The emerging standard of care - Vassilakopoulos, T.P.; Pangalis, G.A.; Katsigiannis, A.; Papageorgiou, S.G.; Constantinou, N.; Terpos, E.; Zorbala, A.; Vrakidou, E.; Repoussis, P.; Poziopoulos, C.; Galani, Z.; Dimopoulou, M.N.; et al. (Oncologist, 2012)
More aggressive treatment approaches (methotrexate, cytarabine, cyclophosphamide, vincristine, prednisone, and bleomycin [the MACOP-B regimen] or consolidation with high-dose therapy and autologous stem cell transplantation) have been considered to be superior to cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) in patients with primary mediastinal large B-cell lymphoma (PMLBCL). Rituximab-CHOP (R-CHOP) is the standard of care for diffuse large B-cell lymphoma, whereas efficacy in PMLBCL has not been adequately confirmed. Patient and Methods. Seventy-six consecutive PMLBCL patients who received R-CHOP with or without radiotherapy (RT) were compared with 45 consecutive historical controls treated with CHOP with or without RT. Baseline characteristics of the two groups were balanced. Results. The rate of early treatment failure was much lower with R-CHOP with or without RT (9% versus 30%; p =.004). The 5-year freedom from progression rate after R-CHOP with or without RT was 81%, versus 48% for CHOP with or without RT (p < .0001). The 5-year event-free survival rates were 80% and 47% (p < .0001) and the 5-year overall and lymphoma-specific survival rates were 89% and 69% (p = .003) and 91% and 69% (p = .001), respectively, with only seven of 76 lymphoma-related deaths. Among R-CHOP responders, 52 of 68 received RT. Conclusions. Based on these results, most patients with PMLBCL appear to be cured by R-CHOP in 21-day cycles with or without RT, which could be the current standard of care. Therefore, the need for more aggressive treatment strategies is questionable unless high-risk patients are adequately defined. Further studies are required to establish the precise role of RT. ©AlphaMed Press.
Keywords: CHOP; Large B-cell lymphoma; Primary mediastinal; Radiotherapy; rituximab; Standard of care